놀이치료자가 지각한 치료적 동맹에 영향을 미치는 내담아동변인 연구 - 강하영; Kang Ha Yeong; 김광웅; Kim Gwang Ung (한국놀이치료학회지(놀이치료연구), 2002)
The purpose of this study was to find out children`s variables(age, gender, patterns of disorder, case history, number of siblings, experience of early education, experience of psychotherapy temperament, social competence) affecting therapeutic alliance and their therapists. The subjects of this study were 64 children, aged three to seven, and their mothers and therapists. In order to analyze the data, the researcher used t-test, simple regression, hierarchical multiple regression, and one-way ANOVA with SAS program. The results of this study were as follows: First, the play therapists` perceived therapeutic alliance was related to temperament characteristics of children. Second, the play therapists perceived that therapeutic alliance on children with emotional and social problems was more easily solidified. On the other hand, children with developmental problems had difficulty in building up therapeutic alliance.